1983
DOI: 10.1007/bf00251826
|View full text |Cite
|
Sign up to set email alerts
|

Cellular composition of the human diabetic pancreas

Abstract: Insulin, glucagon, somatostatin and pancreatic polypeptide cells were stained by immunoperoxidase techniques and quantitated morphometrically in sections of pancreases obtained from eight control subjects, four Type 1 (insulin-dependent) and eight Type 2 (non-insulin-dependent) diabetic patients. The whole pancreas was studied to take into consideration the heterogeneous distribution of the different cell types. From the volume density of each cell type, and the weight of each lobe of the pancreas, the total m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
221
4
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 371 publications
(251 citation statements)
references
References 20 publications
24
221
4
2
Order By: Relevance
“…Hence, insulin-deficient islets composed of normal numbers of alpha cells were found in the autopsied pancreas in 11 children with recent-onset type 1 diabetes [6], and no difference in alpha cell number was found between 11 juvenile diabetic patients and control subjects [7]. Furthermore, the mass of alpha, delta and pancreatic polypeptide cells and the ratio of delta to alpha cells in four type 1 diabetes patients did not differ from those in control subjects [8]. All these findings suggest that beta cells undergo specific damage in autoimmune type 1 diabetes, which may be promoted by the selective recognition of beta cell antigens by T cells.…”
Section: Discussionmentioning
confidence: 90%
“…Hence, insulin-deficient islets composed of normal numbers of alpha cells were found in the autopsied pancreas in 11 children with recent-onset type 1 diabetes [6], and no difference in alpha cell number was found between 11 juvenile diabetic patients and control subjects [7]. Furthermore, the mass of alpha, delta and pancreatic polypeptide cells and the ratio of delta to alpha cells in four type 1 diabetes patients did not differ from those in control subjects [8]. All these findings suggest that beta cells undergo specific damage in autoimmune type 1 diabetes, which may be promoted by the selective recognition of beta cell antigens by T cells.…”
Section: Discussionmentioning
confidence: 90%
“…On the other hand it is possible that SSTRs are upregulated as a defense mechanism against hyperglucagonemia. Previous studies demonstrated a hyperplasia and hypertrophy of pancreatic D-cells in type 1 and type 2 diabetes (Rahier et al, 1983;Orci et al, 1976;Iki and Pour 2007;Gomez Dumm et al, 1995). Thus, both the increase in SST production as well as SSTR Page 9 of 29 A c c e p t e d M a n u s c r i p t 9 expression on A-cells could provide a defense mechanism against hyperglucagonemia; however, experimental evidence supporting this hypothesis remains to be established.…”
Section: Rodentsmentioning
confidence: 96%
“…Patients with type 1 diabetes were reported to have increased number of D-cells, whereas the ratio of Dto A-cells was decreased due to A-cell hyperproliferation (Orci et al, 1976;Rahier et al, 1983). Type 1 diabetic patients had elevated basal plasma SST concentrations (Skare et al, 1985;Segers et al, 1989) and increased responsiveness of pancreatic D-cells to arginine, whereas the overall prandial SST levels was reduced (Skare et al, 1985).…”
Section: Type 1 Diabetes Mellitusmentioning
confidence: 99%
See 1 more Smart Citation
“…In type 2 diabetes, hyperglycaemia has been associated with a deficit in beta cell mass of ∼20-65% of normal [5][6][7][8][9][10][11], and studies in rodent models of autoimmune diabetes or in patients with newly onset type 1 diabetes indicate that the extent of beta cell loss amounts to ∼50-70% around the manifestation of type 1 diabetes [12][13][14]. Diabetes is also frequently found in patients with chronic pancreatitis (CP), secondary to the inflammatory process within the pancreas [15][16][17].…”
Section: Introductionmentioning
confidence: 99%